Between coproduction and commons: understanding initiatives to reclaim urban energy provision in Berlin and Hamburg. Issue 1 (2nd January 2017) - Becker, S.; Naumann, M.; Moss, T.
Abstract : This article explores new geographies of coproduction emerging in urban energy politics. It analyses processes of remunicipalisation of urban utilities, involving the re-establishment of public ownership with a strong democratic and ecological agenda for governing energy infrastructures, with case studies of the German cities of Berlin and Hamburg. Seeking ways of understanding these developments which transcend conventional binaries, such as public vs. private ownership or consumer vs. producer, we interpret them in relation to debates first about coproduction and then about urban commons. This latter concept, we argue, provides deeper analytical purchase on new grassroots energy initiatives and the politics that unfold in remunicipalisation conflicts, offering a new avenue for enriching research on the coproduction of energy.